2011
DOI: 10.1203/pdr.0b013e31820b937d
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Content and Density in Rett Syndrome and Their Contributing Factors

Abstract: This study used densitometry to investigate the areal bone mineral density (aBMD) and bone mineral content (BMC) in an Australian Rett syndrome cohort and assess how factors such as genotype, epilepsy, BMI and mobility affect these parameters. The influence of lean tissue mass (LTM) and bone area (BA) on total body BMC (TBBMC) was also investigated. Participants, recruited from the Australian Rett Syndrome Database (ARSD), had TBBMC and lumbar spine (LS) and femoral neck (FN) aBMD measured using Dual energy X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 30 publications
5
41
2
1
Order By: Relevance
“…172,173 Fracture risk was four times that of the general female population, and specifically increased in those with p.Arg168* and p.Arg270*mutations (see Fig 2). 173 Several Danish, 174,175 US 176,177 and further Australian studies 178,179 have also investigated which particular bone parameters were most adversely affected and their potential nutritional, 180 (e.g. Vitamin D status) environmental and genetic risk factors.…”
Section: Bone Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…172,173 Fracture risk was four times that of the general female population, and specifically increased in those with p.Arg168* and p.Arg270*mutations (see Fig 2). 173 Several Danish, 174,175 US 176,177 and further Australian studies 178,179 have also investigated which particular bone parameters were most adversely affected and their potential nutritional, 180 (e.g. Vitamin D status) environmental and genetic risk factors.…”
Section: Bone Healthmentioning
confidence: 99%
“…For example, right femoral neck areal bone mineral density was particularly impaired with increasing age and lack of mobility in comparison to other parameters. 178 A recent Danish study concluded that the comparatively reduced levels of biochemical bone markers in RTT signified a a low bone turnover state. 182 Nonrepresentative and small sample sizes, often without longitudinal collection, lack of childhood population bone parameter norms and accommodation for decreased stature and different analytical methods all make cross-study comparison difficult.…”
Section: Bone Healthmentioning
confidence: 99%
“…However, in general, studies have reported conflicting associations of the effects of physical activity on bone turnover in different populations (37). Also, DXA studies of the association between bone mass and ambulant ability in RTT have shown diverging results (4,6,7,13,38).…”
Section: Rett Syndrome and Low Bone Turnovermentioning
confidence: 99%
“…Previously, dual-energy x-ray absorptiometry (DXA) studies have reported low bone mass in patients with RTT (4)(5)(6)(7)(8), and increased occurrence of low-energy fractures in these patients has also been shown (9). Patients with RTT are often growth retarded (10).…”
mentioning
confidence: 99%
“…An observational study such as ours identifies factors associated with low bone mineral mass, but they may not be causally related. Small body size, deficits in lean body mass, anticonvulsant use, and nonambulatory status contribute to poor bone mineral status (3,24,29,30). Furthermore, the determination of BMD by dual energy x-ray absorptiometry should be made cautiously in individuals with short stature insofar as smaller, adequately mineralized bones may appear less dense by this method.…”
Section: Discussionmentioning
confidence: 99%